The Relationship Between Inquiry-Based Learning And Arabic Learning For Students Of The Arabic Language Center - Nurdiana, Ryan; Fitriani, Laily; Burhanudin Yusuf, Enjang (TarbiyahMU, 2024)
The study aims to test whether there is a relationship between inquiry-based learning and Arabic learning in students of special Arabic language development programmes at the UIN Maulana Malik Ibrahim Language Centre Unit. The research uses a quantitative approach using simple random sampling techniques. The sample taken was 50 students. This study uses one independent variable, namely inquiry-based learning (X) and one dependent variable; namely Arabic language learning. (Y). The data analysis technique used in this study is simple regression analysis. The result of this study is a known significance value (Sign.) of 0.170 which means less than 0.05 Furthermore, the determination coefficient is obtained with a value of 0.039 or 3.9%, so it can be concluded that the variable x (inquiry-based learning) has a weak relationship to the effect value of 3.9% on the Y variable. (Arabic learning) Keyword : Inquiry-based learning, Arabic learning, Language Centre